Chloride stress corrosion cracking (cscc) of austenitic stainless steel under thermal insulation: Case study analysis - Sivanathan, P. (Asian Research Publishing Network, 2016)
Corrosion under insulation (CUI) is a severe problem for 304 stainless steel pressure vessel. This study is to identify factors responsible for loss of production due to problems in plant and equipment. The combined action of tensile stress with corrosive environment can lead to chloride stress corrosion cracking (CSCC). Chloride stress corrosion cracking initiates from sites of localized pitting or crevice corrosion. The initiation of crack is more dependent on chloride concentration but less dependent on temperature. However, the growth and propagation of a crack is widely affected by temperature and less affected by chloride concentration and pH. In austenitic stainless steel, the main forms of corrosion are pitting and stress corrosion cracking caused by chlorides. In this study the influence of operating conditions such as chloride concentration, temperature on stress corrosion cracking of austenitic stainless steel will be investigated. Corrosion problems arise in situations due to cycling temperatures which vary from below the dew point to above ambient temperatures. The investigations will be carried out under thermal insulation, which modifies the local corrosion conditions and it has never been investigated to the best of our knowledge. At the end of the research, the conditions where SCC occurs will be defined and documented. Â© 2006-2016 Asian Research Publishing Network (ARPN). All rights reserved.